The Influence of Perceptions of Convenience, Benefits, and Risks on Interest in Using Financial Technology (Gopay) in Gen Z in Bandar Lampung City - Lusiana Putri; Muhammad Iqbal; Rahmat Fajar Ramdani (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the effect of perceptions of convenience, benefits, and risks to the interest of Generation Z in using financial technology (GoPay) in the city of Bandar Lampung. This study uses a descriptive quantitative approach with sampling techniques through the Slovin formula, which resulted in 100 respondents from Generation Z in the region. Data analysis was conducted using PLS-SEM method through SmartPLS 4 application, covering validity, reliability, hypothesis test, and coefficient of determination. Overall, this study consistently shows that perceptions of ease, benefit, and risk have a positive and significant influence on Gen Z's interest in using GoPay fintech in Bandar Lampung City. The three proposed hypotheses proved to be accepted, with benefit perception and risk perception showed a stronger influence than the perception of ease based on the value of T-statistics and f-square. Specifically, the R-Square value of 0.673 confirms that this model is very good at explaining the 67.3% variation in interest in GoPay use by Gen Z. These results support the validity of the Technology Acceptance Model (TAM) and provide practical implications for fintech service providers to prioritize improving perceived benefits and effective risk management, while maintaining ease of use, to drive continued adoption and interest among the Gen Z segment.